Study of The Properties of Radiation Shielding Using Epoxy with BeO, MgO, TeO2, and Bi2O3 Compounds - Rajab, Mustafa Y.; Mohammad, Kareem K. (Iraqi Journal of Science, 2026)
The technological development and the radiation use in various fields, industry, medicine, agriculture, scientific research, etc., and getting on the principle of As Low As Reasonably Achievable (ALARA) in protection radiation, shielding is one of the important protection rules, representing placing different materials between the radiation sources and the object to reducing the intensity of radiation and protected. Samples of composite materials were prepared with different reinforcing elements and epoxy as the fundamental substance. BeO, MgO, TeO3, and Bi2O3 with various ratios 10, 20, 30, and 40% with diameter 2.5 cm and high 2 cm were prepared to study the effect of these materials on the Half Value Layer (HVL), Tenth Value Laye (TVL), and mean free path (MFP) as examples of attenuation coefficients, in addition to basic coefficients linear and mass attenuation. These parameters were measured using sodium iodide system NaI(Tl) gamma spectroscopy (2"×2") after irradiation with gamma ray at energy 661 keV from the radioactive source Cs-137. The results showed that these coefficients are affected by the addition of reinforcing materials with epoxy and lead to attenuation of gamma-ray intensity. The linear attenuation coefficient was increased with an increase in the atomic number and ratio of the reinforcing materials. At the same time, the (HVL) decreased, proving the availability of using some composite as gamma-ray shielding.